2007
DOI: 10.1093/deafed/enm017
|View full text |Cite
|
Sign up to set email alerts
|

Reading Comprehension of Deaf Children With Cochlear Implants

Abstract: The reading comprehension and visual word recognition in 50 deaf children and adolescents with at least 3 years of cochlear implant (CI) use were evaluated. Their skills were contrasted with reference data of 500 deaf children without CIs. The reading comprehension level in children with CIs was expected to surpass that in deaf children without implants, partly via improved visual word recognition. Reading comprehension scores of children with implants were significantly better than those of deaf children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 31 publications
7
69
1
4
Order By: Relevance
“…Readers may be surprised that more of the good readers did not have cochlear implants; however, it must be noted that the age of implantation for these children ranged from 3 years 10 months to 5 years 8 months and so these were not early implanted. The advantage in reading ability typically found for cochlear implanted deaf children is usually observed in early implanted children (see Archbold, Harris, O'Donoghue, Nikolopoulos, White & Richmond, 2008;Vermeulen, van Bon, Schreuder, Knoors & Snik, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Readers may be surprised that more of the good readers did not have cochlear implants; however, it must be noted that the age of implantation for these children ranged from 3 years 10 months to 5 years 8 months and so these were not early implanted. The advantage in reading ability typically found for cochlear implanted deaf children is usually observed in early implanted children (see Archbold, Harris, O'Donoghue, Nikolopoulos, White & Richmond, 2008;Vermeulen, van Bon, Schreuder, Knoors & Snik, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of large cohorts in Scotland (Thoutenhoofd, 2006) and the Netherlands (Vermeulen, van Bon, Schreuder, Knoors, & Snik, 2007) found that children with cochlear implants scored comparatively higher on reading and writing than peers with hearing aids but were still delayed when compared to hearing peers. In all three of these studies, which were carried out some years ago, children with a range of cognitive abilities were included.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors (e.g. Merrills, Underwood, & Wood, 1994;Vermeulen, van Bon, Schreuder, Knoors & Snik, 2007;Wauters et al, 2006) argue that deaf children's reading comprehension delays are not simply a consequence of their poor visual word recognition skills. For example, both Wauters et al (2006) and Vermeulen et al (2007) reported that visual word recognition scores (from lexical decision tasks) only accounted for between 32% and 52% of the variation in reading comprehension skills in deaf children with and without cochlear implants.…”
mentioning
confidence: 99%